The effect of sweet and salty taste sensitivity on gin-gival health in relation to salivary serotonin among type1 diabetic patients aged 12-14 years - Rasool , Tabarak A; Diab , Ban S (Journal of Baghdad College of Dentistry, 2022)
Background: This study was conducted among diabetic persons to assess the sweet and salty taste sensitivity with its effect on gingival health in relation to salivary serotonin levels. Materials and methods: A cross-sectional comparative study design was used. All patients with diabetes aged 12-14 years that attend the Paediatric hospital at Baghdad medical city with specific inclusion criteria were involved in the sample of the present study (patients group 50 patients) compared with non-diabetic persons matched in age and gender of the study sample (control group 70 patients) who were attending dental unit in the college of dentistry/university of Baghdad. A two-alternative forced choice question including each component presented at five different quantities was used to evaluate the threshold sensitivity of salt and sweet taste, sub-sample of 44 subjects was recruited from each group and matched in age and gender for salivary analysis and serotonin measurement and gingival health status was measured by using the gingival index. Results: Data analysis of this study revealed that the occurrence of the highest sweet threshold was found among diabetic persons with no significant difference. The data revealed no significant difference in the mean gingival index while salivary serotonin value was lower in diabetic subjects with a significant difference; meanwhile, it showed no significant relation with both taste thresholds. Conclusions: Within the limitation of this study, it was observed, that diabetes did not affect salty and sweet taste thresholds in addition to gingival health. Whereas salivary serotonin had a role among the diabetic patients by which it was lower among diabetic subjects.